Social media : an additional channel for effective crisis communication. - Tan, Hui Lin. (2010)
Social media has been receiving a lot of attention from companies due to the large number of users that are engaged in it. A worldwide Nielsen study has shown that there is a 82% increase in users spending more than five hours a day on social networking sites in December 2009 since a year ago.